Formulir RASCANDIS 1.0: Pendekatan Terapi Anti-Kandida Sistemik untuk Pasien Non-Transplantasi - Natadidjaja, Ronald Irwanto; Ariyani, Aziza; Adlani, Hadianti; Dharmayanti, Anti; Bratanata, Joyce (Jurnal Biomedika dan Kesehatan, 2023)
It has been a concern that using antifungals may induce some fungi to develop antifungal resistance in the future. Therefore, systemic anti-candidiasis agents should become a focus in controlling antifungal drugs since it is quite commonly used. There are currently three approaches to using systemic anti-candidiasis agents based on their indication, i.e. definitive, empiric and pre-emptive indication. These can be applied by observing supportive findings such as the presence of Candida sp infection or colonization, the severity of the infection and the patient's risk factors. The severity of invasive candidiasis is usually severe, and various risk factors need to be considered, such as Total Parenteral Nutrition (TPN), catheterization including deep vein catheter, central venous catheter (CVC), etc.  Antifungal stewardship program, including management of systemic anti-candidiasis, is essential nowadays. Therefore, it is necessary to have a program that can serve as a guideline for clinicians to implement a treatment approach for systemic anti-candidiasis. RASPRO Alur Anti Candida Sistemik (RASCANDIS) 1.0 form or the Indonesian Regulation on the Prospective Antimicrobial System on Systemic Anti-Candidiasis Flowchart 1.0 form is an actual implementation to provide guidelines for clinicians to administer systemic anti-candidiasis agents for non-transplant patients. The form is not a diagnostic tool, but it is more likely to serve as a review and summary of knowledge obtained from various scientific journals, which is expected that it can be proposed as an effort to administer therapeutic management of systemic anti-candidiasis appropriately.